Serum Zonulin Measured by Commercial Kit Fails to Correlate With Physiologic Measures of Altered Gut Permeability in First Degree Relatives of Crohn's Disease Patients - Power, Namita; Turpin, Williams; Espin-Garcia, Osvaldo; Smith, Michelle I.; , The CCC GEM Project Research Consortium; Croitoru, Kenneth (Frontiers in Physiology, 2021)
Intestinal epithelial cell tight junctions (TJs) contribute to the integrity of the intestinal barrier allowing for control of the physical barrier between external antigens or bacterial products and the internal environment. Zonula occludens-1 (ZO-1) is a protein that modulates intestinal TJs, and serum levels of ZO-1 has been suggested as a biomarker of disrupted barrier function in humans. Previous studies suggested that increased intestinal permeability was associated with evidence of TJ abnormalities. However, there is limited information on the serological measurement of ZO-1 and its relation to other tests of barrier function in healthy subjects. We investigated the correlation of serum ZO-1, with physiologic measures of intestinal permeability (as the ratio of the fractional excretion of lactulose-mannitol or LMR) in a cohort of 39 healthy FDRs of Crohn’s disease (CD) patients. No significant correlation was found between LMR and ZO-1 levels (r2 = 0.004, P<0.71), or intestinal fatty acid binding proteins (I-FABP) (r2 = 0.004, P<0.71). In conclusion, our data show that ZO-1 and I-FABP are not a marker of gut permeability as defined by LMR.